2010
DOI: 10.1017/s0007114510001923
|View full text |Cite
|
Sign up to set email alerts
|

Total fluid and specific beverage intake and mortality due to IHD and stroke in the Netherlands Cohort Study

Abstract: Chronic mild dehydration has been associated with several diseases, including fatal IHD and stroke. It has been suggested that hydration through total fluid intake (or water) is inversely associated with IHD or stroke mortality. The objective of the present study was to evaluate the relationship between total fluid (and specific beverage) intake and IHD or stroke mortality in the Netherlands Cohort Study (NLCS). In 1986, 120 852 participants aged 55 -69 years were enrolled into the NLCS. Mortality data were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 45 publications
1
49
3
Order By: Relevance
“…Therefore, in women, the suggestion of a slight increase in risk of mortality that was seen when high total water intake was due to plain water intake was unexpected. This study finding is contrary to results from reports of an inverse association of fluid or water intake with risk of heart disease and certain cancers (12)(13)(14)(15), which may have been expected to lead to a favorable mortality outcome. The possibility that the observed association may have been spurious because of multiple-hypothesis testing or because of the methodologic limitations later discussed could not be excluded and requires confirmation from other cohorts with comparable exposures and outcomes.…”
Section: Tablecontrasting
confidence: 99%
See 1 more Smart Citation
“…Therefore, in women, the suggestion of a slight increase in risk of mortality that was seen when high total water intake was due to plain water intake was unexpected. This study finding is contrary to results from reports of an inverse association of fluid or water intake with risk of heart disease and certain cancers (12)(13)(14)(15), which may have been expected to lead to a favorable mortality outcome. The possibility that the observed association may have been spurious because of multiple-hypothesis testing or because of the methodologic limitations later discussed could not be excluded and requires confirmation from other cohorts with comparable exposures and outcomes.…”
Section: Tablecontrasting
confidence: 99%
“…The association of water intake and body-weight management has also received considerable attention (11). However, the meager published evidence on modification of risks of leading chronic diseases such as heart disease, cancer, and diabetes has largely been limited to plain water or fluid intake (12)(13)(14)(15)(16)(17)(18). To our knowledge, intakes of total water and individual sources of ingested water in relation to health have received relatively little scrutiny.…”
Section: Introductionmentioning
confidence: 99%
“…In the Adventist Health Study, fatal coronary heart disease was significantly lower among participants who drank ≥5 cups of water daily compared with <2 cups [21], however no association was seen for high intakes of beverages other than water. In a Dutch cohort, neither total fluid intake nor plain water intake predicted fatal ischemic heart disease or stroke over 10 years of follow-up [66], however another prospective study found a significantly reduced risk of stroke recurrence among patients whose total self-reported water intake was >2 l/day compared with ≤2 l/day [26]. …”
Section: Discussionmentioning
confidence: 99%
“…8 In contrast, in a small cohort study of 499 hypertensive and nonsmoking men (including 76 total stroke events), the risk of ischemic stroke was 2.1-fold higher for men who consumed 3 cups of coffee per day as compared with nondrinkers. 9 Most cohort studies of coffee consumption in relation to stroke mortality among healthy women and men 10,11 or among diabetics 12,13 have found no association. However, in a cohort study of Japanese women and men, coffee consumption was significantly inversely associated with stroke mortality among men but not in women.…”
Section: Discussionmentioning
confidence: 99%